A Tangled Web: Assessing overlaps between energy and environmental policy instruments along the electricity supply chain. (31st July 2015) - Simoes, Sofia; Huppes, Gjalt; Seixas, Julia
Abstract: In OECD countries, many overlapping energy and environmental policy instruments are targeting the various stakeholders in the electricity supply chain (producers, transmission and distribution companies and various consumers). Although synergies between different policy instruments exist, e.g. reducing acidification and climate change by reducing energy consumption, there are also measures whose effects counter each other. Such counter effects arise not only within different environmental policy instruments but also with energy policy instruments. This paper surveys the overlaps in the policy instruments that target the European Union electricity system and characterizes their interactions. A framework for further assessment and analysis of overlaps and co‐effects between policy instruments is presented. The development of policies and their implementation using specific instruments may then be better aligned. A brief discussion on how trade‐offs can be structured is made, as well as some notes on issues to be considered towards policy integration. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment